1992
DOI: 10.1177/026988119200600115
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam-induced retrieval impairments revealed by the use of flumazenil: a study in surgical dental patients

Abstract: Twenty-one outpatients attending Guy's Dental Hospital received intravenous midazolam prior to the removal of at least one wisdom tooth. The patient's memory for material presented both before and after midazolam was assessed either whilst still in the drug-treated condition (midazolam+placebo) or in the drug-reversed condition (midazolam+flumazenil). There were no differences between the two retrieval conditions in the number of words or pictures correctly recalled or recognized and both groups showed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…It is therefore the expression of a genuine drug effect. Evidence that lorazepam impairs semantic memory performance has already been reported by Bacon et al (1998) using a generalknowledge task: This tallies with the findings of File et al (1992b), who showed that midazolam, another benzodiazepine, impairs word-completion performance. It is also consistent with Vermeeren et al (1995), who reported that lorazepam subjects made more errors than placebo subjects in a sentence verification task.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is therefore the expression of a genuine drug effect. Evidence that lorazepam impairs semantic memory performance has already been reported by Bacon et al (1998) using a generalknowledge task: This tallies with the findings of File et al (1992b), who showed that midazolam, another benzodiazepine, impairs word-completion performance. It is also consistent with Vermeeren et al (1995), who reported that lorazepam subjects made more errors than placebo subjects in a sentence verification task.…”
Section: Discussionsupporting
confidence: 81%
“…They have consistently been shown to induce a transient anterograde amnesia that lasts a few hours Bishop & Curran, 1995;Curran et al, 1993;Danion, 1994;Danion et al, 1989Danion et al, , 1992Danion et al, , 1993File et al, 1992aFile et al, , 1992bLegrand et al, 1995;Pompéia et al, 1996;Vidailhet et al, 1996;Weingartner et al, 1993). All these studies examining the effects of benzodiazepines on memory have focused on the amount of information retained or retrieved.…”
Section: Introductionmentioning
confidence: 99%
“…This is in keeping with the majority of studies on the effects of benzodiazepines (Lister, 1985;Ghoneim and Mewaldt, 1990). However, we have previously found that a higher dose of midazolam (0.13 mgkg) does impair retrieval from semantic memory as measured by the word gap completion test (File et al, 1992). Lorazepam (2.5 mg) has previously been found to impair recency judgements (File, 1992a,b) and the results of the present study suggest that midazolam (0-075 m@g) also impairs these judgements.…”
Section: Discussionsupporting
confidence: 46%
“…In general, benzodiazepines have been found not to impair retrieval from semantic memory, but we have found impaired performance of a word completion task after midazolam and lorazepam when subjects were given words with gaps (File et al, 1992;File, 1992a,b). Furthermore, lorazepam has been shown to impair judgements of recency (File, 1992a).…”
Section: Introductionmentioning
confidence: 52%
“…Similarly, in a study on temporal information processing and memory, the benzodiazepine midazolam significantly reduced integrity of performance on time estimation [6], Since, in previous studies, midazolam has been shown to cause deterioration of memory functions [75][76][77] and, furthermore, a highly significant correlation between performance on free recall and performance on time estimation for the midazolam group was found, decreasing task accuracy was attributed to midazolaminduced impairment of memory functions [6]. According ly, the deteriorating effects of haloperidol and remoxipride on performance on time estimation may have been caused by drug-induced impairment of memory pro cesses.…”
Section: Temporal Processing and Dopaminementioning
confidence: 99%